(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
One of the important tasks of economic entities operating in our republic is to develop this sector through tax incentives, introduce new approaches to them, increase the volume of market services, and expand opportunities for the population to create new jobs. In addition, the benefits used by enterprises in order to develop certain sectors of the economy, prevent an increase in prices for socially significant products and services, as well as provide social support to local producers and all segments of the population are covered.